Anagrelide influences thrombotic risk, and prolongs progression‐free and overall survival in essential thrombocythaemia vs hydroxyurea plus aspirin. (1st July 2020) - Kellner, Adam; Dombi, Peter; Illes, Arpad; Demeter, Judit; Homor, Lajos; Ercsei, Ibolya; Simon, Zsofia; Karadi, Eva; Herczeg, Jozsef; Gy Korom, Viktoria; Gasztonyi, Zoltan; Szerafin, Laszlo; et al.
Abstract: Objective: We report an extension study of patients with essential thrombocythaemia (ET) in the Hungarian Myeloproliferative Neoplasm (HUMYPRON) Registry, which demonstrated that over 6 years anagrelide significantly decreased the number of patients experiencing minor arterial and minor venous thrombotic events (TEs) vs hydroxyurea+aspirin. Methods: Data on patients with ET were collected through completion of a questionnaire developed according to 2008 WHO diagnostic criteria and with regard to Landolfi, Tefferi and IPSET criteria for thrombotic risk. Data were entered into the registry from 14 haematological centres. TEs, secondary malignancies, disease progression and survival were compared between patients with ET treated with anagrelide (n = 116) and with hydroxyurea+aspirin (n = 121). Results: Patients were followed for (median) 10 years. A between‐group difference in the number of patients with TEs was observed (25.9% anagrelide vs 38.0% hydroxyurea+aspirin; P  = .052). Minor arterial events were more frequently reported in the hydroxyurea+aspirin group ( P  < .001); there were marginally more reports of major arterial events in the anagrelide group ( P  = .049). TE prior to diagnosis was found to significantly influence TE incidence ( P  > .001). Progression‐free survival ( P  = .004) and survival ( P  = .001) were significantly increased for the anagrelide group vs hydroxyurea+aspirin. Conclusions: Anagrelide reduced TEs, and increased progression‐free and overall survival vs hydroxyurea+aspirin over (median) 10 years.